Результаты оценки перспектив нефтегазоносности участков расположения импактных структур частотно-резонансным методом обработки данных дистанционного зондирования Земли - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н.; Прилуков, В.В. (Геоінформатика, 2016)
Анализируются результаты оценки перспектив нефтегазоносности участков расположения крупного импактного кратера Сильян в Швеции, локального поискового участка в его пределах, а также двух небольших структур на территории США. Экспериментальные исследования проведены с использованием мобильной прямопоисковой технологии частотно-резонансной обработки и интерпретации данных дистанционного зондирования Земли (ДЗЗ), которая работает в рамках “вещественной” парадигмы геофизических исследований. В процессе выполнения исследований метод оперативной оценки максимальных значений пластовых давлений флюидов в коллекторах был усовершенствован — дополнен возможностью оценки давлений в различных (в том числе глубинных) интервалах разреза. На площади расположения кратера Сильян обнаружено и закартировано 16 аномальных зон типа “газ”, “нефть + газ”, “газ + вода”, а в пределах локального участка — 6 аномалий типа “газ” и “газ + вода”. Значения пластового давления флюидов варьируют в пределах аномалий в интервале от 2,2 до 8,0 МПа. Пробуренные в кратере Сильян скважины (в том числе глубокие Gravberg-1 и Stenberg-1) не попадают в контуры обнаруженных аномалий. На площади расположения кратера Panther Mountain (США) обнаружено шесть аномальных зон типа “залежь газа”, а на поисковой площади “Big Basin” (США) — пять аномалий типа “нефть + газ” и четыре — типа “газ”. Обнаруженные аномалии следует считать локальными участками для первоочередного детального изучения геофизическими методами и разбуривания. Это по сути зоны “sweet spots”. Результаты исследований свидетельствуют о наличии в пределах импактных структур локальных участков и зон, перспективных на обнаружение скоплений углеводородов (УВ) в коммерческих объемах. Применение мобильных методов “прямых” поисков скоплений УВ в районах распространения коллекторов и структур различного типа будет способствовать значительному повышению коэффициента успешности бурения (увеличению количества скважин с коммерческими притоками УВ). Усовершенствованная методика оценки пластовых давлений флюидов в различных горизонтах разреза может найти широкое применение для оперативной оценки перспектив нефтегазоносности глубинных горизонтов разреза. Наличие значительного количества аномальных зон типа “залежь нефти и газа” (в том числе в кристаллических породах на глубине) в пределах кратера Сильян, расположенного на Балтийском щите, можно считать дополнительным свидетельством в пользу абиогенного происхождения УВ. Проаналізовано результати оцінювання перспектив нафтогазоносності ділянок розташування великого імпактного кратера Сильян у Швеції, локальної пошукової ділянки в його межах, а також двох невеликих структур на території США. Експериментальні дослідження проведено з використанням мобільної прямопошукової технології частотно-резонансної обробки та інтерпретації даних дистанційного зондування Землі (ДЗЗ), яка працює в рамках “речовинної” парадигми геофізичних досліджень. У процесі виконання досліджень метод оперативної оцінки максимальних значень пластових тисків флюїдів у колекторах було вдосконалено — доповнено можливістю оцінювання тисків у різних (у тому числі глибинних) інтервалах розрізу. На площі розташування кратера Сильян виявлено та закартовано 16 аномальних зон типу “газ”, “нафта + газ”, “газ + вода”, а в межах локальної ділянки — 6 аномалій типу “газ” і “газ + вода”. Значення пластового тиску флюїдів варіюють у межах аномалій в інтервалі від 2,2 до 8,0 МПа. Пробурені в кратері Сильян свердловини (у тому числі глибокі Gravberg-1 та Stenberg-1) не потрапляють у контури виявлених аномалій. На площі розташування кратера Panther Mountain (США) знайдено шість аномальних зон типу “поклад газу”, а на пошуковій ділянці “Big Basin” (США) — п’ять аномалій типу “нафта + газ” і чотири типу “газ”. Виявлені аномалії слід вважати локальними ділянками для першочергового детального вивчення геофізичними методами та розбурювання. Це по суті зони “sweet spots”. Результати досліджень свідчать про наявність у межах імпактних структур локальних ділянок і зон, перспективних на виявлення скупчень вуглеводнів (ВВ) у комерційних обсягах. Застосування мобільних методів “прямих” пошуків скупчень ВВ у районах поширення колекторів і структур різного типу сприятиме значному підвищенню коефіцієнта успішності буріння (збільшенню кількості свердловин із комерційними припливами ВВ). Удосконалена методика оцінювання пластових тисків флюїдів у різних горизонтах розрізу може знайти широке застосування для оперативної оцінки перспектив нафтогазоносності глибинних горизонтів розрізу. Наявність значної кількості аномальних зон типу “поклад нафти і газу” (в тому числі у кристалічних породах на глибині) в межах кратера Сильян, розташованого на Балтійському щиті, можна вважати додатковим свідченням на користь абіогенного походження ВВ. Purpose. The purpose of the paper is to evaluate hydrocarbon potential of the areas of large Siljan impact crater location in Sweden, the local exploration block within it, and two small structures in the United States; to select the optimal sites within the surveyed areas for exploration wells laying, to study the possibility of using direct-prospecting remote methods to detect meteorite fragments location; to develop and improve the techniques of geophysical direct-prospecting methods and technologies application during oil and gas prospecting and exploration in the reservoirs of conventional and unconventional types.
Design/methodology/approach. Experimental studies were conducted using the mobile direct-prospecting technology of remote sensing (RS) data frequency-resonance processing and interpretation, which operates within the “matter” Paradigm of Geophysical Research. The method of an operative assessment of the fluid pressure maximum values in the reservoirs is an important component of this technology. In the course of the investigations, this method was improved by adding the ability of the reservoir pressure assessment in various intervals of cross-section, included depths).
Findings. In the area of the Siljan crater location we discovered and mapped 16 anomalous zones of the “gas”, “oil + gas”, “gas + water” type and 6 anomalies of the “gas” and “gas + water” type within the local area. Values of fluid pressure in reservoirs vary within anomalies, ranging from 2,2 to 8,0 MPa. According to the scanning data, one gas-saturated horizon and four horizons with water and gas were located at the top of the cross-section. Using the technique of the reservoir pressure assessing at different intervals of the section within the “Gas” anomalous zone, the following additional intervals for searching were identified: 1) 420—500 m, H = 80 m; 2) 1120—1150 m, H = 30 m; 3) 2880—3140 m, H = 260 m;
4) 5185—5195 m, H = 100 m. The drilled wells in the Siljan crater (Gravberg-1 and Stenberg-1 deep wells included) does not fall within the contours of the detected anomalies. In the area of the Panther Mountain crater location (USA), six anomalous zones of the “reservoir of gas” type were found. In the anomalous zone “Gas-1”, three intervals of possible accumulation of gas were identified — two intervals in the anomalous zone “Gas-2” and one interval in other four anomalies. In the “Big Basin” search area (USA), five anomalous zones of the “oil + gas” type and four anomalous zones of the “gas” type were mapped. Within the anomalies contours, two intervals promising for oil and gas accumulations detection were found. The observed anomalies should be considered as priority local areas for detailed study by geophysical methods and drilling. In effect, these are “Sweet spots” zones.
Practical value/implications. The results of the studies indicate the presence, within impact structures, of local areas and zones promising for the commercial hydrocarbon accumulation. The use of mobile and operative methods of “direct” prospecting for hydrocarbon accumulations in the areas of various type of reservoir (collectors) and structure spreading could significantly improve the success rate of drilling (i.e. an increase in the number of wells with commercial hydrocarbon inflows). The improved method of fluid pressure in reservoir estimation at different levels of the cross-section can be widely used for the operative assessment of hydrocarbon potential of the cross-section deep horizons. The presence of a significant number of anomalous zones of the “oil and gas deposit” type (in crystalline rocks at depth included) within the Siljan crater located on the Baltic Shield can be regarded as additional evidence in favor of the abiogenic origin of hydrocarbons.